Bosnia and Herzegovina : Financial Sector Assessment Program Technical Note-Systemic Liquidity Management, Financial Safety Net, Insolvency Framework, and Macroprudential Policy. (IMF Staff Country Reports; Country Report, 2015)
This Technical Note discusses key findings and recommendations of the assessment on Systemic Liquidity Management, Financial Safety Net, Insolvency Framework, and Macroprudential Policy on Bosnia and Herzegovina. It is observed that there are constraints on the ability of both banks and the Central Bank of Bosnia and Herzegovina to manage liquidity. The system lacks a central bank liquidity window, and the secondary market for government securities is also small and illiquid. Liquidity regulations should be streamlined and the adoption of the liquidity coverage ratio would strengthen liquidity management. The deposit insurance framework is a relatively well-developed paybox scheme, but further enhancements of the deposit insurance arrangements would be beneficial.